Penyuluhan Fisioterapi Komunitas Terkait Postur Tubuh untuk Meningkatkan Pengetahuan Siswi Kelas 7 SMPS Al-Fattah Kabupaten Malang - Dhea Armelia Suryani; Rakhmad Rosadi; Ratna Vidya Amelia (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Good posture during activities is a body position that uses little energy to keep the body balanced and comfortable. When the body position tends to be bad, it will also result in incorrect posture if done repeatedly during activities. The impacts that can occur are postural abnormalities such as kyphosis, scoliosis, and lordosis. Incorrect body position during activities, inappropriate forms of learning support, and incorrect use of backpacks can hurt body posture. If the body posture is in good condition, it will support the students' learning activities. Conversely, if the body posture is in bad condition, it will also have an impact on their education. This counseling activity aims to increase the knowledge of the students regarding how to have good body posture. To make it easier for the students to understand the things conveyed, the presentation of the material was carried out using the leaflet method as a printed media which was distributed to 40 students at SMPS Al-Fattah. The results of the counseling were seen through pre-test and post-test data that had been processed so that in this counseling activity it can be concluded that there was an increase in students' knowledge about how to have good and correct body posture.